Case report: Severe dry cough associated with superior vena cava syndrome—Caused recurrent chylothorax - Wan, Ziming (Frontiers in Cardiovascular Medicine, 2022)
Introduction Symptomatic pleural effusion is occasionally caused by superior vena cava syndrome. Dyspnea and pleuritic chest pain are common symptoms of pleural effusion. However, the current literature has not reported a causal linkage between chylous pleural effusion and dry cough. Case presentation A patient with uremia suffered from an unexplained severe dry cough, which could be triggered by postural changes. Medical examinations ruled out the possibility of chronic bronchitis, gastroesophageal reflux, chest tumor, tuberculosis, asthma, chronic obstructive pulmonary disease, and allergy history. Examinations showed that the patient had chylous pleural effusion. The cough symptoms were relieved after extraction of the pleural effusion but soon reappeared with the recurrence of chylothorax. Enhanced computed tomography showed that the patient had superior vena cava occlusion. After recanalization of the superior vena cava by percutaneous balloon dilatation, the patient no longer had chylothorax, and the severe cough was eliminated. Conclusion Super vena cava syndrome can cause chylothorax and further stimulate severe dry cough. Cough is not a specific symptom. Chest imaging and pleural fluid analysis can help narrow down the diagnosis.